(untitled) (Contemporary Journal of Social Science Review, 2025)
Quinoa is a nutrient-rich pseudo-cereal, providing essential nutrients such as protein, fiber, vitamins, and minerals. Adding quinoa to biscuits can enhance their nutritional profile, making them a healthier snack compared to traditional biscuits made solely with fine flour. Quinoa has been a staple food in the Andean region of South America for thousands of years, particularly in countries like Peru, Bolivia, and Ecuador. Its cultural significance extends beyond its nutritional value, playing a vital role in traditional ceremonies. Quinoa contains all nine essential amino acids, making it a complete protein source. By incorporating quinoa into biscuits, you can increase the protein content of the final product, which can be beneficial for individuals looking Consuming quinoa has been associated with various health benefits, including improved digestion, reduced risk of certain chronic diseases, and better weight management. By including quinoa in biscuits, you can offer a snack or treat option that not only tastes good but also supports overall health and well-being. to boost their protein intake, especially those following vegetarian or vegan diets. While making quinoa biscuits three methods are adopted. The first method the percentage of quinoa was 70 and the percentage of wheat flour was 30 and the second method of making biscuits the percentage of wheat flour was 70 and percentage of quinoa was 30. The 3rd method of making quinoa biscuits the percentage of quinoa was 90%. After these three methods we identify different results Some experiments are performed in lab like moisture and ash analysis. The percentage of moisture analysis is 5.88 and the percentage of ash analysis is 5.17. Study shows different results from three methods the biscuits which have 70% quinoa are healthier but the taste of biscuits is little bit bitter due to high content of quinoa and low content of sugar. In second method which we use 30% quinoa are sweat and good taste and their nutritional profile is also good. In 3rd method which we use 90% quinoa for making biscuits are very sour and their taste is not good so we identify the 30% of quinoa biscuits are much better from these 2 methods.